Emotional Resonance in Islamic Podcasts: A Study on Listener Loyalty and Religious Learning - Nazar Nazar; Helga Helga; Rifai’i Rifai’i; N. Baskautshar (Tinta Emas Institute, 2024)
This study examines how emotional resonance shapes listener loyalty and Increasing Religious Learning in Islamic podcasts, with listening satisfaction and trust acting as parallel mediators. Using a quantitative approach, data were collected through an online questionnaire from 750 loyal Islamic podcast listeners in Indonesia and analyzed with Structural Equation Modeling (SEM) using AMOS. The results show that emotional resonance significantly increases listening satisfaction and trust, listening satisfaction significantly enhances listener loyalty, and trust has a strong positive effect on Increasing Religious Learning. In addition, there is a significant total indirect effect of emotional resonance on Increasing Religious Learning through the combined roles of listening satisfaction, trust, and listener loyalty (β = 0.40, p < 0.001). The structural model demonstrates strong explanatory power, accounting for 68% of the variance in listener loyalty and 59% of the variance in Increasing Religious Learning. These findings confirm the pivotal role of emotional connectivity in digital religious communication and provide a validated structural model that offers empirical guidance for Islamic podcast content creators to optimize engagement and learning outcomes by strategically fostering emotional resonance, listening satisfaction, and trust